SISTEM INFORMASI HARGA POKOK PROSES BAGI USAHA KECIL DAN MENENGAH DALAM MENINGKATKAN KUALITAS PROSES PRODUKSI - Agus Dwi Atmoko; Danis Imam Bachtiar; Supriono Supriono (AKSES: Jurnal Ekonomi dan Bisnis, 2014)
Accounting Information Systems today has an important role to the progress of an organization included in the business world. The problem that often arises in small and medium enterprises, among others on the system transactions are still done manually, by relying on paper for archiving enterprise data. Of course, such things will be difficult to control and report transaction data namely finance Production Cost and Process Cost. An application system that can help the process along with the transaction data report is required which can present useful information for interested parties to address such problems. The fact that there are still many small and medium-class companies (SMEs) still doing transaction processing, financial records and preparing reports both reports transactions and financial statements of the company manually. Improving the IT mastering is one of the important factors that need to be considered for small and medium enterprises and it also can develop the business wheel. IT development has been moving very rapidly, both in terms of hardware and software which can help the company's performance.One of SMEs in Kebumen district is tile company famous brand of Sokka. Most companies tile in the district Kebumen still use manual accounting system. Tile Company Brands Sokka does the production process using the production machine. Where the process Brands Sokka tile production company produces several kinds of products in the form types of tile press generated from period to period is always the same.The existence of accounting information system is expected to make management transactions and corporate finance better and accurate, and can help entrepreneurs and policy makers in managing the company's finances and taking policy’s company as well as scoring at the performance of the company. Therefore, the authors apply a Cost Information System applications Process For Small And Medium Enterprises In Improving the Quality of Production Process using microsoft office 2007 program. Keywords: Information Systems, Production Cost, Process Cost